1H NMR foodomics reveals that the biodynamic and the organic cultivation managements produce different grape berries (Vitis vinifera L. cv. Sangiovese). (15th December 2016) - Picone, Gianfranco; Trimigno, Alessia; Tessarin, Paola; Donnini, Silvia; Rombolà, Adamo Domenico; Capozzi, Francesco
Highlights: The influence of biodynamic agronomical practice on grape composition is studied. A shift toward a more anaerobic metabolism in biodynamic berries is observed. Proline, valine and isoleucine concentrations are higher in biodynamic grapes. Abstract: The increasing demand for natural foods and beverages, i.e. prepared by excluding synthetic chemicals along the whole production chain, has boosted the adoption of organic and biodynamic cultivation methods which are based on protocols avoiding use of synthetic pesticides. This trend is striking in viticulture, since wine production is largely shaped by the varying drinking attitudes of environment-friendly consumers. Using 1 H NMR, the compositions of grape berries, collected at harvest in 2009 and 2011, in experimental plots cultivated either with biodynamic or organic methods, were compared. Although the analysis provides a comprehensive metabolic profile of berries, the resulting distinctive pattern consists of a few molecules. Lower content of sugars, coumaric and caffeic acids, as well as higher amount of γ-aminobutyric acid (GABA) were observed in biodynamic grapes. The 1 H NMR foodomics approach evidenced a diverse fruit metabolome that could be associated to a different physiological response of plants to the agronomic environment.